X-ray characterization of anisotropic defect formation in SiC under irradiation with applied stress. (May 2021) - Koyanagi, Takaaki; Sprouster, David J.; Snead, Lance L.; Katoh, Yutai
Abstract: High-energy x-ray diffraction is employed to gain insight into the irradiation-induced creep behavior of silicon carbide (SiC). Polycrystalline β-SiC specimens were simultaneously exposed to elevated temperature neutron-irradiation and mechanically applied stresses. The structural disordering was subsequently examined using two-dimensional x-ray diffraction. The intensity of the (111) shoulder peak, an indication of stacking disorder, increased when the specimens were irradiated under tensile stress. This is the first observation of nanoscale stress-induced stacking disorder in SiC at low neutron fluences. These findings suggest stress-induced preferential nucleation and/or growth of defect clusters as a key creep mechanism in neutron irradiated SiC. Graphical abstract: Image, graphical abstract